Nephelium Lappaceum Seed As Natural Coagulant Flocculant For Landfill Leachate Treatment - Rahmat, Nur Syahirah (Universiti Sains Malaysia, 2017)
Landfill leachate produced from landfilling has caused pollution risk to environment due to the harmful and toxic content if directly discharged into environment. Chemical based coagulants and flocculants are commonly used in coagulation – flocculation process. However, the drawbacks of using these chemical materials have triggered researchers to find natural materials to substitute or reduce the amount of chemical based coagulants and flocculants. Nephelium lappaceum seed has been chosen in this study as natural coagulant/flocculant to treat landfill leachate from Alor Pongsu Landfill Site (APLS). The effectiveness of the seed was determined through a series of jar tests by finding the best operational conditions (pH and dosages) for Nephelium lappaceum seed and SnCl4 as coagulant. The performance of coagulants was measured through the removal efficiencies of colour, suspended solids (SS), and chemical oxygen demand (COD). Results indicated that Nephelium lappaceum seed as sole coagulant could remove 19.48% of colour, 35.62% of COD, and 0% of SS at the best conditions which is pH 6 with dosage of 2 g/L. Meanwhile, SnCl4 as sole coagulant could remove high percentage of pollutants which is 98.22% of SS, 88.86% of colour, and 84.22% of COD at pH 7 with 10.50 g/L of SnCl4. Nephelium lappaceum seed is not effective as SnCl4 when used as sole coagulant, but it shows excellent performance in removing pollutants as flocculant with SnCl4 as primary coagulant and thus, has accomplished the aim of reducing the amount of SnCl4 from 10.50 g/L to 8.40 g/L with removal efficiencies of 88.86% colour, 87.57% SS, and 75.94% COD. Besides that, the effectiveness of Nephelium lappaceum seed can be further proven with sludge performance and settleability. Nephelium lappaceum seed helps in improving the sludge performance and settleability by increasing flocs size, density of flocs, sludge settling velocity as well as sludge volume index. In conclusion, Nephelium lappaceum seed has a potential to be used as natural flocculant with chemical based coagulant to treat landfill leachate treatment and this could reduce the usage of chemical based coagulant and improve the sludge settling performance.